A Commentary on Sport and Terrorism From the Vantage of Sport Psychology. (August 2016) - Schinke, Robert J.; McGannon, Kerry R.; Busanich, Rebecca; Ge, Yang
The authors of this article engage in a commentary regarding broad thematic areas identified within the special issue on sport and terrorism. The commentary begins with the authors situating themselves within the field of sport psychology, and as critical scholars more specifically within the emerging cultural sport psychology genre. To further contextualize certain aspects of criticality outlined from a sport psychology vantage, a brief story is offered where one of the authors shares his experience as a volunteer during the 1996 Olympics as a volunteer, where he was first exposed to sport and terrorism. Next, discussions are taken up in relation to four themes that we identified as relevant from the foregoing sport psychology vantage: (a) sport events and terrorism as mainstream, (b) terrorism and the media as conduit, (c) sport as a recruitment tool toward and away from terrorism, and (d) sport as an antidote to terrorism. The commentary authors conclude with a summation followed by parting critical reflections in relation to the current and future status of this emerging area.